(untitled) (World Science, 2020)
The study was aimed to establish the features of configuration of generalized pаrodontal diseases and their clinical manifestations in the format of basic characteristics of anorexia nervosa. We used clinico- radiological, immunological, analytical and statistical methods. Thus, direct correlation and interdependence of generalized parodontal diseases in the format of basic characteristics of anorexia nervosa were established.